IRAN IN DIE INTERNASIONALE MAGSTRYD - Gerber, M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Iran, once the state which, in the midst of political turmoil and military conflict among its Arab neighbours, enjoyed an era of unprecedented economic prosperity and social stability under the administration of the Shah - was suddenly plunged in 1978 into a cultural crisis whose central theme was the common Islamic faith of otherwise diverse groups with disparate political and ideological aspirations. The Iranian revolution, however, was never a merely regional affair, although it started against the background of purely local political issues. The Persian state, in point of fact, became the focal point of centrifugal power struggle between the superpowers, which had already spread to the entire geopolitical area of the Persian Gulf. Meanwhile, it is apparent that the revolution in Iran has left a power vacuum in the region – the country had previously enjoyed close military ties with the US and has played an important security role for the West in acting as a bulwark against Communist domination of the region. With the Islamic state now wavering between a policy of uncommitted neutrality and closer association with the Arabic world, it is possible that continuing internal unrest will lead to the vacillating Bazargan Government giving way to the demands of Communist pressure groups, which enjoy significant support in the workforce of the manufacturing and oil industries.